No Time For Old Men – Effect Of Corona Lockdown On Elders - Dr. Ritu Bhattacharyya, Dr. Sangita Kohli, Dr. Raghavendra S Bendigeri, Sampurna Nand Mehta (International Journal of Advanced Science and Technology, 2020)
Purpose –The purpose of this paper is to find out the situation of elders during the lockdown announced by the Government. The study also aims to find out if the Government had taken into consideration the problems of the elders before they decided to lockdown.